Body composition and somatotype of the elite of Polish fencers - Sterkowicz-Przybycien, K. (Collegium Antropologicum, 2009)
The purpose of this study was to determine body composition and somatotype of the male fencers who were grouped by different fencing weapons. Analysis of body composition, with untrained men as background, will update the data necessary for the somatic profiles of fencers. Thirty contestants were examined during the Polish Fencing Championships in 2004. They took part in épée (n=10), foil (n=10) and sabre (n=10). They were aged 23.3±2.9; their length of training was 12.6±2.5 years, with the frequency of training 15.9±3.1 hours per week. In each weapon style there were champions and vice-champions of Poland from the year 2004. Twelve of them were classified among the first fifty contestants according to the D`Escrime International Federation (FIE) ranking. An experienced evaluator performed 10 measurements necessary to designate somatotypes by means of Heath-Carter method and to estimate the percentage of body fat and composition. Sabre fencers (weight=84.4 kg, somatotype=3.4-5.4-1.8) were heavier than both épée fencers (77.9 kg, 3.6-4.9-2.5) and foil fencers (74.9 kg, 2.9-4.2-2.8). Sabre specialists had higher mesomorphy than foil fencers (ANOVA and Bonferroni`s multi comparison test). Sabre fencers were characterized by higher fat free mass and a higher BMI and fat free mass index than fencers of the other two weapons. Discriminant analysis result was significant (p<0.01) with a relative percentage with a 72.4 and a canonical correlation coefficient 0.692, and Wilks` l=0.385. Amongst the 30 observations used to fit the model, 22 (73.3%) were correctly classified. Against the background of non-training men, fencers were distinguished by a higher body weight (79.0 vs. 72.1 kg, t=3.97, p<0.001) and a higher height-weight ratio (43.21 vs. 42.46, t=2.24, p<0.05). Fencers` somatotypes differed from the somatotypes of the untrained (3.3-4.8-2.3 vs. 3.7-4.3-3.1). They were characterized by their higher mesomorphy (t=2.10, p<0.05) and lower ectomorphy (t=3.48, p<0.01), as well as greater adiposity (16.8 vs. 15.7%, t=2.03, p<0.05).